2014
DOI: 10.1371/journal.pone.0105618
|View full text |Cite
|
Sign up to set email alerts
|

Deprived TLR9 Expression in Apparently Healthy Nasal Mucosa Might Trigger Polyp-Growth in Chronic Rhinosinusitis Patients

Abstract: BackgroundThe origin of nasal polyps in chronic rhinosinusitis is unknown, but the role of viral infections in polyp growth is clinically well established. Toll-like receptors (TLRs) have recently emerged as key players in our local airway defense against microbes. Among these, TLR9 has gained special interest in viral diseases. Many studies on chronic rhinosinusitis with nasal polyps (CRSwNP) compare polyp tissue with nasal mucosa from polyp-free individuals. Knowledge about changes in the turbinate tissue bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Probably partly due to differences in the study set up, they demonstrated a more apical location of TLR3 and an increase in expression of TLRs 2, 3, 4 proteins following the allergen challenge pre-season, but an increase only in TLR3 mRNA during the pollen season (29 in polyp tissue, whereas TLR9 was absent in turbinates from CRSwNP patients. CpG stimulation resulted in an upregulation of TLR9 and modulation of cytokines in turbinate tissue from patients, suggesting that defects in the TLR9 mediated microbial defense in the turbinate might explain virus-induced polyp growth (37). Several studies have observed TLRs in the atopic lower airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Probably partly due to differences in the study set up, they demonstrated a more apical location of TLR3 and an increase in expression of TLRs 2, 3, 4 proteins following the allergen challenge pre-season, but an increase only in TLR3 mRNA during the pollen season (29 in polyp tissue, whereas TLR9 was absent in turbinates from CRSwNP patients. CpG stimulation resulted in an upregulation of TLR9 and modulation of cytokines in turbinate tissue from patients, suggesting that defects in the TLR9 mediated microbial defense in the turbinate might explain virus-induced polyp growth (37). Several studies have observed TLRs in the atopic lower airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, epithelial expression of TLR9 was detected in turbinates from healthy controls and in polyp tissue, whereas TLR9 was absent in turbinates from CRSwNP patients. CpG stimulation resulted in an upregulation of TLR9 and modulation of cytokines in turbinate tissue from patients, suggesting that defects in the TLR9-mediated microbial defense in the turbinate might explain virus-induced polyp growth [ 77 ].…”
Section: Disrupted Epithelium During Chronic Upper Airway Diseasesmentioning
confidence: 99%
“…Several studies have reported that whole mucosal tissue and epithelial‐specific TLR9 expression is decreased in CRSwNP. For instance, Tengroth et al . found from CRSwNP patients that TLR9 expression was decreased in turbinate epithelial cells, and Lauriello et al .…”
Section: Discussionmentioning
confidence: 99%